1998
DOI: 10.1046/j.1365-277x.1998.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating cognitive behavioural therapy into dietetic practice: a challenge for dietitians

Abstract: Historically, State Registered Dietitians have not received in‐depth training in behaviour change skills. Training in this area has been viewed as peripheral rather than fundamental. Whilst a permanent long‐term cure for obesity remains elusive, cognitive behavioural therapy is state of the art in the treatment of obesity. It reliably achieves 10% pretreatment body weight loss in the short‐term. Interesting new developments are occurring in this field which may affect long‐term outcome favourably. This paper e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…This was echoed in a UK dietetic survey where cognitive behavioural therapy skills were highlighted as requiring further attention (Rapoport, 1998). There have been calls for interpersonal skills to become a central aspect of dietetic practice, (Rapoport, 1998; Isselmann et al. , 1993; Long et al.…”
Section: Skills and Competenciesmentioning
confidence: 99%
“…This was echoed in a UK dietetic survey where cognitive behavioural therapy skills were highlighted as requiring further attention (Rapoport, 1998). There have been calls for interpersonal skills to become a central aspect of dietetic practice, (Rapoport, 1998; Isselmann et al. , 1993; Long et al.…”
Section: Skills and Competenciesmentioning
confidence: 99%
“…It is well established that the provision of advice and information about any health behaviour does not necessarily mean that a person will change that behaviour, and this includes eating and physical activity behaviours . In fact, direct persuasion from an expert in order to improve health or reduce risks to health often results in quite low adherence to advice . As obesity is now a major public health concern, the role of the dietician is paramount .…”
Section: Introductionmentioning
confidence: 99%
“…Hickman stated that dieticians must embrace BT and lifestyle interventions, and that training should reflect this, including ongoing reflection and up‐skilling in such competencies for existing dieticians. Earlier, Rapoport noted that training in behaviour change skills for dieticians has traditionally been viewed as peripheral, but recommended that behavioural psychology and counselling skills become core components of training. She found that most dieticians think that training in CBT would be useful or very useful and were keen to learn new skills that may benefit their clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations